A Social Learning Approach to Strategic Management: Toward a Theoretical Foundation - Ginter, Peter M.; White, Donald D. (Academy of Management Review, 1982)
Repeated calls have been made for a general theory of strategic management that will enhance research, teaching, and application of subject matter in the area. This paper presents a social learning theory of strategic management (SLTSM) that encompasses earlier attempts to explain strategic management and offers a distinctive conceptual framework. SLTSM links the interdependent elements of executive cognition, stimulus and consequence environments, and strategic behaviors, through reciprocal determinism, providing a unique perspective on strategic management.